PREDIKSI CURAH HUJAAN MENGGUNAKAN METODE E. J. GUMBEL UNTUK RENCANA SISTEM PENYALIRAN TAMBANG - Nurfajar, Ilham Rifki; Purwana, Rachmadhi; Soelarno, Soemarno W. (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
The Tailings Storage Facility (TSF) is one of the largest constructions in mining activities involving sediment ponds that is an important and common facility used in mining activities. This study aims to recommend safe and environmentally friendly water management in settling ponds. This research is done by analyzing rainfall using E. J. Gumbel Method and designing a mine drainage system. The prediction results produce a maximum rainfall of 20.99 mm/day and a rain intensity value of 7.28 mm/hour. The catchment area is 380,355 m2 and the total runoff water discharge is 0.64 m3/second. Runoff water enters the settling pond with a volume of 2,438 m3/day. The capacity of the 3 (three) compartments of settling ponds is 4,500 m3 and an area of 500 m2.